STRATEGI KOMUNIKASI DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN INDRAGIRI HULU DALAM PELAKSANAAN PROGRAM LAYANAN ASPIRASI DAN PENGADUAN ONLINE RAKYAT (LAPOR) - Alhikmah Munawaroh; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The district government Indragiri Hulu is one of 303 local governments have partnership with service of aspiration and complaints of the people online program (LAPOR) central and And it’s the first district that socialize and conducted LAPOR in province of Riau. People using program LAPOR in district of Indragiri Hulu were amount of 725 users from throughout the community. The purpose of this research is to know the communicators election strategy, message, media, an effect or feedback, and the completion of the LAPOR systems of the implementation program LAPOR in district of Indragiri Hulu.This research used qualitative approach. The subject of research determined base on technique purposive that comprising head office of Diskominfo Inhu, head of management ICP, head of section for public information management, head of section partnership ICP, functional general staff, and two people students that has been received socialization of LAPOR program. Technique data collection is interview, onservation, and documentation. Technique analysis data is data of reduction, presentation of data, and conclusion. Technique is the extension of participation and triangulation.The research result showed that strategy Diskominfo Inhu in the implementation of program LAPOR is the communicators or the source of information that convey information about the program LAPOR work at the LAPOR central and administrator district that has been received training of program LAPOR. The message was using sentence informative, persuasive, educational, and obvious. The media that in use is the printed media, electronic media such as radio, and new media like online media and social media. An effect or feedback is being able to benefit and help people in doing repert dan reduce the abusing status. The settlement of the problem have been carried out with verify report and disposing to administrator of regional device organization.Keywords: strategy communications, LAPOR